The Determinants of Sovereign Credit Ratings: Indonesia and Its Neighborhood Countries 1998-2016 - Solikin, Akhmad; Michel, Gerry (Universitas Muhammadiyah Prof. DR HAMKA., 2019)
The aim of this research is to study the determinants of sovereign credit ratings of Indonesia andits neighborhood countries in the period of 1998-2016. Using secondary data and analyzed usingordered probit, it is found that every credit rating agency has its own variables influencing to itspublished credit ratings.In general, for Indonesia and its neighborhood countries, the variables withsignificant and positive relationship are fiscal balance and current account deficit to GDP, freedomindex, and GDP per capita; while the variables with significant and negative relationship are externaldebt to GNI and real exchange rate. Gross domestic savings to GDP influences credit ratings inboth ways. Interestingly, inflation does not affect the credit ratings. Indonesia and neighborhoodgovernments could use this information to manage their macroeconomic indicators in order to getfavorable ratings from credit rating agencies.